Ambidexterity, performance and environmental dynamism. Issue 3 (6th March 2017) - Tamayo-Torres, Javier; Roehrich, Jens K.; Lewis, Michael A.
Abstract : Purpose: The purpose of this paper is to examine the relationship between organizational ambidexterity, the ability of companies to explore new and to exploit existing processes simultaneously, and manufacturing performance as represented by the sand cone model. Moreover, the paper analyses the impact of stable and dynamic environments on this relationship. Design/methodology/approach: A set of research questions are tested using structural equation modeling on a sample of 231 Spanish manufacturing companies. Findings: Results illustrate a significant relationship between ambidexterity as the basis and enabler for manufacturing performance improvements, building on the sand cone model and its dimensions of quality, delivery, cost, and flexibility. This relationship is further emphasized when companies work in a dynamic environment. Practical implications: The study contributes to practice by investigating the important and yet under-explored relationships of ambidexterity, the sand cone model, performance, and a company's wider market environment. Findings suggest a positive relationship between the sand cone model and ambidexterity capability. Originality/value: This study adds to the limited theoretical and empirical understanding of the relationships between ambidexterity, the sand cone model, environmental dynamism, and performance. It also contributes through a set of empirical data derived from Spanish manufacturing companies.